Podeželje Svečinskih goric - Drozg, Vladimir (Revija za geografijo, 2018)
The purpose of this text is the geographical representation of Svečinske gorice hills, which is based on the current and new contents of the landscape. We selected six thematic sections: natural disasters in the area, socio demographic caracteristics of population, changes in cultural landscape, economic structure of the area, quality of living environment and phenomenon of nerby border. The hills of Svečinske gorice are a mix of agrarian and urban. The concentration of both features is the element of the regional differentiation. In eastern and south-eastern part of Svečinske gorice, urban elements dominate over agrarian, while in the northern and western part, the more pronounced is the agrarian landscape.
Keywords: geografija podeželja; regional geography; regionalna geografija; rural geography; Slovenia; Slovenija; Svečinske gorice